Carbon Nanotubes Recent Advances, New Perspectives and Potential Applications - Muzibur Rahman, Mohammed; Mohammed Asiri, Abdullah; Asaduzzaman Chowdhury, Mohammad (IntechOpen, 2023)
Carbon Nanotubes - Recent Advances, New Perspectives and Potential Applications covers all the important nanotechnological aspects of carbon materials, including their growth and characterization, processing and fabrication, development and potential applications. Recent developments, innovative preparation methods and promising new frontiers around this advanced nanotechnology are reviewed under the editorship of an internationally renowned scientist. This book will be useful to a diverse range of readers and will be important for research organizations, government research centers, academic libraries, and those involved in the research and development of carbon materials.